Impact of ECE on Social Competencies and Language Learning - Ahmad Bilal Cheema, Mushtaq Ahmad, Safia Perveen (JECCE, 2023)
Early childhood education (ECE) addresses holistic development of the children brings positive experiences and enhances academic and social competencies. In Pakistan, ECE program was started in last two decades with limited budget. Recent educational policies and projects have focused ECE by developing rooms, play facilities and leaning kits, learning material and Teachers training etc. This casual comparative study compared the public ECE and Public non ECE students in social development and language learning. Sample of 300 students from public ECE and public non ECE institutions was selected for studying level of social competency and 500 for measuring academic achievement in English and Urdu language by two stage stratified random sampling technique. To compare mean social competencies scores and language achievement scores of public ECE and public non ECE students, t-test was used. The study found that students studying in public ECE institutions are better in social competencies and language learning than that of students in public non ECE schools.